2004
DOI: 10.1258/000456304323019596
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes of insulin-like growth factors and their binding proteins throughout normal pregnancy

Abstract: Background Insulin-like growth factors (IGFs) are anabolic proteins that are essential regulators of cell division, differentiation and growth. We describe the longitudinal changes in IGF-I, IGF-II and the binding proteins IGFBP-1, -2 and -3 before and during normal pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 52 publications
9
20
1
Order By: Relevance
“…However, as discussed previously [21], their nutritional status is probably typical of that of Swedish women and not very different from women in other developed countries. Regarding the variability of the maternal IGF system components before, during and after pregnancy, our observations were similar to those reported for other study populations [4, 10, 13]. The changes we observed during pregnancy are also in agreement with results obtained in other Western populations for IGF-I [4, 10, 13], IGF-II [4, 10, 13], IGFBP-1 [4, 10], IGFBP-3 [10, 11, 13] and protease activity against IGFBP-3 [13,14,15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, as discussed previously [21], their nutritional status is probably typical of that of Swedish women and not very different from women in other developed countries. Regarding the variability of the maternal IGF system components before, during and after pregnancy, our observations were similar to those reported for other study populations [4, 10, 13]. The changes we observed during pregnancy are also in agreement with results obtained in other Western populations for IGF-I [4, 10, 13], IGF-II [4, 10, 13], IGFBP-1 [4, 10], IGFBP-3 [10, 11, 13] and protease activity against IGFBP-3 [13,14,15].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, serum concentrations of IGF-I decrease during the first trimester [4, 10] and increase gradually throughout the remaining two trimesters [4,10,11,12,13], whereas concentrations of IGF-II remain relatively unchanged throughout gestation [10, 13]. The serum concentrations of IGFBP-3 increase gradually during pregnancy [4, 10], while those of IGFBP-1 are increased in the first trimester and remain high until delivery [4, 10, 12, 13]. In addition, during pregnancy, IGFBP-3 is degraded by proteases to a considerable extent [13,14,15], possibly produced by the decidua [14].…”
Section: Introductionmentioning
confidence: 99%
“…Last, first-trimester IGF-I could be a proxy for nonpregnant exposure to IGF-I at a given age. Circulating IGF-I during the first half of the pregnancy is fairly constant and similar to the concentrations measured before the index pregnancy or in age-matched nonpregnant women (30,(32)(33)(34)(35), although some recent longitudinal studies suggested that a decline in maternal IGF-I around 8 to 16 weeks of pregnancy may occur (33,34,36). However, the data from the largest and well-designed longitudinal study published thus far indicate that despite the drop in mean IGF-I during early pregnancy, there is still an important degree of correlation between preconception and 8-week-gestation IGF-I (r 2 = 0.32, corresponding to r = 0.57; ref.…”
Section: Discussionsupporting
confidence: 55%
“…In the first and second trimester of a normal pregnancy binding proteins for IGF-I rapidly and drastically increase but total IGF-I levels fall whereas IGF-II levels increase after correction for pregnancy related hemodilution. In a recent study there were decreases of IGF-I during the first trimester of more than 30% and of more than 20% during the second trimester and a rise in the last trimester of 25% [21] (Fig. 3).…”
Section: Age Gender and Pregnancy Dependent Factorsmentioning
confidence: 72%